HUBUNGAN MAYORITAS HINDU BALI TERHADAP MINORITAS MUSLIM (Studi Toleransi Puri Pemecutan Terhadap Komunitas Minoritas Muslim di Kampung Bugis Serangan, Denpasar-Bali) - Rusmayani, Rusmayani; Gunawan, Agus Hendra (Institut Agama Islam Riyadlatul Mujahidin (IAIRM) Ngabar Ponorogo, Indonesia, 2018)
Hindu society is the majority in Bali Island, however it is able to live harmoniously against the minority of Muslim community in Bali. This aim of study for 1) 1) knowing the form of relationship and tolerance of religious life between Hindus (Puri Pemecutan) and Bugis Village Muslims, 2) the efforts of the majority of Hindus (Puri Pemecutan) in realizing and maintaining the tolerance of religious life with the Muslims of Kampung Bugis, Serangan. This research is a qualitative descriptive research, with unstructured interview data collection techniques, observation, and documentation. The data were analyzed with stages data reduction, data presentation, and inference. The results of research is 1) the form of tolerance of religious life seen in various aspects of life, among others a) the king often attended the event of the Maulid Nabi, breaking fast together, and halal bi halal, rather than the king often wearing sarong and kopiah, b) When there is otonan or wedding of Puri Pemecutan family, king always invites Muslims Bugis and Muslims participate in the event such as donating rodat,of art. 2) Efforts to realize and maintain the relationship of tolerance based on their respective teachings. The tolerance was taught to his descendants by continuing to connect intertwining silaturrahim. They were invited and visited each other when there are big days or family event, social activity, and help each other in aspect of life.